2023
DOI: 10.47191/ijsshr/v6-i2-66
|View full text |Cite
|
Sign up to set email alerts
|

Character Education in the Perspective of Imam Asy-Sya'rani

Abstract: This research aims to examine Imam As-Sya'rani's perspective of the moral values contained in the book of Al Minah Al Saniyah. Imam As-Sya'rani's thoughts have their value in serving as a guide in inculcating moral education and character building. That becomes relevant when looking closely at the implementation of moral education, which only touches on cognitive aspects and has not yet touched on affective (inner) aspects. By touching the minds of students, moral education can shape human character with good … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Fourth, Aminaturrahma et al (2023) research entitled The Impact of Social Media Digitalization on Four Arabic Language Skills. This study discusses the impact of social media digitization on four Arabic language skills, namely Maharah al-Istima ', al-Kalam, al-Qira'ah, and al-Kitabah. The results showed that digitizing social media can improve students' ability to speak Arabic.…”
Section: Introductionmentioning
confidence: 99%
“…Fourth, Aminaturrahma et al (2023) research entitled The Impact of Social Media Digitalization on Four Arabic Language Skills. This study discusses the impact of social media digitization on four Arabic language skills, namely Maharah al-Istima ', al-Kalam, al-Qira'ah, and al-Kitabah. The results showed that digitizing social media can improve students' ability to speak Arabic.…”
Section: Introductionmentioning
confidence: 99%